1983
DOI: 10.1002/star.19830350802
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopy of Enzyme‐digested Starch Granules

Abstract: The study deals with comparison of the susceptibility to fungal glucoamylase and salivary α‐amylase of starch granules from navane, panivaragu, black pepper and black gram. The crude glucoamylase was purified by fractionation and column chromatography to give two pure fractions of which one was used. The rate of amylolysis was followed by estimating the amount of glucose and maltose released. The type and extent of damage of the starch granules were observed by scanning electron microscopy which revealed chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 27 publications
(1 reference statement)
0
7
0
Order By: Relevance
“…It clearly showed that there were many small micropores on the surface. These were the normal micropores in microporous corn starch hydrolyzed by glucoamylase 3.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It clearly showed that there were many small micropores on the surface. These were the normal micropores in microporous corn starch hydrolyzed by glucoamylase 3.…”
Section: Resultsmentioning
confidence: 97%
“…Alpha‐amylases from Bacillus subtilis and glucoamylases from Aspergillus niger have the strongest hydrolytic ability toward starch 1, 2. Among the microporous starches, corn starch is more easily hydrolyzed by glucoamylase and has more inerratic matrix 3. Therefore, corn starch was selected as material to prepare microporous starch by glucoamylase.…”
Section: Introductionmentioning
confidence: 99%
“…The digestibility of starches by amylases is known to be influenced by the amylose content of the starch (Smith, 1982). Bhat et al (1983) also noted in addition that the susceptibility of starches to amylases depends on the degree of polymerization and the presence of non-reducing ends on the starch surface. However higher levels (60 -75%) of amylose has been reported to also resist amylolysis (Paramahans and Tharanathan, 1982).…”
Section: Resultsmentioning
confidence: 97%
“…The purified standard α-amylase also showed maximum dextrinization time at 3h with all the starches but it produced higher concentrations of glucose from the starches (35%, 34% and 33.6% glucose from maize, cassava and potato starches respectively) than the crude α-amylases. The observed variation in dextrinization time was attributed to differences in the susceptibility of the starches to amylolysis due to differences in starch composition (Bhat et al, 1983). Figure 3 shows the effect of reaction time on the saccharification performance of the crude glucoamylase.…”
Section: Effect Of Starch Concentrationmentioning
confidence: 99%
See 1 more Smart Citation